Listener's reaction to post-rock music and western classical music / Leander Samuel Jaun Anak Dominic - Dominic, Leander Samuel Jaun (Faculty of Music, 2017)
This research thesis comprises an compare how much of the listener's reaction or their analysis towards the music relates to the actual analysis of the both genre. For this research, I chose a Post-Rock Music and a piece from the Western Classical Music, specifically from Romantic Era. The attention here is to research and discover whether the listener's reactions to both pieces matches the actual features/analysis of the music.